Recurrence pattern with respect to two different dose fractionations in patients with locally advanced head and neck cancer treated with chemoradiation using image‐guided volumetric arc therapy. Issue 7 (10th May 2022) - Deshmukh, Jayashree; Chatterjee, Abhishek; Dora, Tapas Kumar; Bose, Subhadeep; Goel, Alok; Kakade, Amol; Saini, Amit; Pahwa, Shefali; Singh, Avtar; Laskar, Sarbani Ghosh; Agarwal, Jay Prakash; Shrivastava, Shyam Kishore; et al.
Abstract: Background: Patients with head and neck cancer were treated with either 70 Gy in 35 fractions (Arm A) or 66 Gy in 30 fractions (Arm B). Materials and methods: Total 168 patients of carcinoma oropharynx, larynx, and hypopharynx treated with radical chemoradiation in two Arm A versus B (65 vs. 103 patients). Results: With a median follow‐up of 16 months (0–67), 2 year disease‐free survival (DFS) and overall survival (OS) was 56.3% versus 62.1% ( p  = 0.64) and 44.5% versus 53.0% ( p  = 0.51) in Arm A versus B. Total 22 (33.8%) versus 28 (27.2%) failed locoregionally. Majority of failures were infield for both primary (17 vs. 23 cases) and nodes (13 vs. 12) in Arm A versus B. Ten (71.4%) vs. 10 (76.9%) had nodal failure in index nodal level only. Conclusion: Commonly seen failure in head–neck radical chemoradiation is within infield high‐risk volume, nodal failure being most common in index nodal level.